Research quality key to higher varsity rankings - Borneo Post, (KK) (Borneo Post, 2017)
PETALING JAYA: Seven Malaysian universities are in Times Higher Education's (THE)inaugural Asia-Pacific University Rankings. Of these, five are in the top 200 with Universiti Putra Malaysia (UPM) and Universiti Teknologi Malaysia (UTM) joint top for Malaysia.